2018
DOI: 10.1111/josi.12287
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture‐Based Protective Factors on Reducing Rates of Violence among African American Adolescent and Young Adult Males

Abstract: Rates of violence in the United States have steadily declined over the last decade. However, there continues to be a disproportionate number of homicides among African American young men compared to their race and gender counterparts. Among African American males between the ages of 15–24, homicide is the leading cause of death. This is a public health issue that seems very preventable and a plethora of research and interventions have explored psychosocial causes that might aid in reducing rates of violence. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
(38 reference statements)
1
10
0
2
Order By: Relevance
“…As a result, the findings of the current study is to be considered with the significance of the above factors [34]. For example it has been suggested that culture and tradition play important roles in reduction of violence and abuse among family members [35]. It is therefore necessary to understand the effect of culture and tradition on the relationship between sisters and brothers, which seems to prevent them from substance use or other behavior disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the findings of the current study is to be considered with the significance of the above factors [34]. For example it has been suggested that culture and tradition play important roles in reduction of violence and abuse among family members [35]. It is therefore necessary to understand the effect of culture and tradition on the relationship between sisters and brothers, which seems to prevent them from substance use or other behavior disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, as relações estabelecidas pelos participantes podem ter construído uma estrutura a partir da qual eles obtêm apoio social, por meio de outras pessoas, ou ainda ajuda espiritual. Diante disso, uma pesquisa de Wallace et al (2018) mostrou que as variáveis espiritualidade, identidade racial e senso de pertencimento à comunidade atuaram como fatores de proteção em uma amostra de jovens afro-americanos do sexo masculino, reduzindo as chances de envolvimento dos participantes em comportamentos violentos.…”
Section: Fatores De Proteção Relacionados Ao Contextounclassified
“…Faz-se necessário, portanto, expandir os conhecimentos acerca dos aspectos pessoais, processuais, contextuais e temporais dos fatores capazes de proteger o ser humano vivendo em condições de adversidade e vulnerabilidade. No âmbito dos comportamentos violentos, o senso de pertencimento à comunidade e a identidade racial também foram identificados como fatores de proteção, assim como a religiosidade (WALLACE et al, 2018). Quanto ao comportamento de violência sexual, especificamente, Salazar et al (2018) demonstraram que o conhecimento sobre consentimento sexual e a dinâmica familiar funcional agiram como fatores de proteção em uma amostra de estudantes universitários do sexo masculino.…”
Section: Introductionunclassified
“…given the findings, one must also consider that the PFRJR may be missing items that are specifically salient in promoting desistance for racial/ethnic minority juveniles. For example, resilience scholars have suggested that protective factors such as adaptability (Wright & Younts, 2009) and ethnic socialization (Wallace et al, 2018) may be particularly important for promoting desistance among racial minority youth. Evidence of differential predictive validity might also be indicative of racial bias in the justice system such as in juvenile arrests rates or the risk assessment process.…”
Section: Race/ethnicitymentioning
confidence: 99%